Tropical landscape evolution and its relationship with paleosurfaces, Ferralsols and ferruginous duricrusts in the Alto Paranaíba region (Central Plateau, Minas Gerais, Brazil) - Marques, Karina Patricia Prazeres (2021)
Latossols, also known as Oxisols and Ferralsols, occur in ancient landscapes in the intertropical zone. They are usually developed on more or less flat surfaces, and at different elevation levels, developed from different parent materials. Although these soils have been extensively studied, several issues remain poorly understood about their formation and evolution in ancient landscapes. Therefore, an area with predominance of Ferralsols, including ferruginous duricrusts, in the Central Plateau (Southwest of the Minas Gerais State, Brazil) was selected to investigate the formation and evolution of thick highly weathered soils, and their relationship with the landscape in which they occur. The contextualization and understanding of the controlling factors responsible for the landscape evolution were carried out (Chapter 2) and, based on this geomorphological understanding, the selection of sites for the study of pedons representative of Ferralsols on the two main identified landforms was carried out, one at the summit and the other at an intermediate level. Systematic sampling reaching several meters deep was carried and samples were collected from different horizons. Samples of the pisolitic horizon from a ferruginous duricrust underlying one of the pedons sampled on the upper and older surface were thoroughly investigated for their mineralogy. (U-Th)/He dating was carried out to constrain the formation and transformation of pisolitic structures, which provide clues to unveil the main weathering periods of the study area (Chapter 3). Samples of the non-indurated horizons were analysed regarding to their chemical composition and mineralogical characteristics, including crystallographic and thermal properties. The weathering conditions that prevailed during their formation were discussed considering the different forming factors (Chapter 4).